2022
DOI: 10.1007/s40820-022-00988-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in One-Dimensional Micro/Nanomotors: Fabrication, Propulsion and Application

Abstract: Due to their tiny size, autonomous motion and functionalize modifications, micro/nanomotors have shown great potential for environmental remediation, biomedicine and micro/nano-engineering. One-dimensional (1D) micro/nanomotors combine the characteristics of anisotropy and large aspect ratio of 1D materials with the advantages of functionalization and autonomous motion of micro/nanomotors for revolutionary applications. In this review, we discuss current research progress on 1D micro/nanomotors, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 188 publications
0
15
0
Order By: Relevance
“…22,23 Over the past 10 years, in order to improve the adsorption efficiency of materials, researchers have proposed different strategies. 24,25 Li et al 26 reported for the first time a single crystalline with ordering of macro-micropores MOF (SOM-MOF), synthesized through the doublesolvent method and hard-template approaches, which displays an ordered hierarchical porous structure ( pore size >100 nm) with perfect mass diffusion as well as single-crystalline properties. Thus, owing to the macro-microporous structure, and especially the pH sensitivity and excellent biocompatibility, ordered macro-microporous zeolitic imidazolate framework-8 (SOM-ZIF-8) particles have great potential for the efficient adsorption of antigen proteins as well as their delivery in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Over the past 10 years, in order to improve the adsorption efficiency of materials, researchers have proposed different strategies. 24,25 Li et al 26 reported for the first time a single crystalline with ordering of macro-micropores MOF (SOM-MOF), synthesized through the doublesolvent method and hard-template approaches, which displays an ordered hierarchical porous structure ( pore size >100 nm) with perfect mass diffusion as well as single-crystalline properties. Thus, owing to the macro-microporous structure, and especially the pH sensitivity and excellent biocompatibility, ordered macro-microporous zeolitic imidazolate framework-8 (SOM-ZIF-8) particles have great potential for the efficient adsorption of antigen proteins as well as their delivery in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Theses magnets are used in plenty of industrial applications: electric machines [1], mechanical damping [2] [3], braking [4] or contactless transmission [5] systems. In MEMS (Micro-ElectroMechanical Systems) [6][7][8] and micromachines [9][10][11][12], high quality magnets of NdFeB and SmCo in micrometric size are required. Small micro magnets have been used in several small applications such as sensors [13], actuators [14,15] [16] robotic manipulators [17] [18], and medical devices [19], in particular, actuators [20] [21] and wireless intrabody power transmission systems [22].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, trimer-like microrobots can employ up to two locomotion mechanisms, depending on whether planar rotating or conical RMFs are applied. [4] Although, the development of soft body magnetic robots has bolstered their adaptability by permitting a broader range of locomotion mechanisms, [5,6] their morphological adaptability remains limited, especially within channels smaller than the size of the robot.…”
Section: Introductionmentioning
confidence: 99%